1987
DOI: 10.1128/jvi.61.12.3820-3826.1987
|View full text |Cite
|
Sign up to set email alerts
|

Detection of latency-related viral RNAs in trigeminal ganglia of rabbits latently infected with herpes simplex virus type 1

Abstract: Using a combination of in situ hybridization and Northern (RNA) blot analysis, we investigated herpes simplex virus type 1 (HSV-1) transcriptional activity in an ocular rabbit model of HSV-1 latency. Radioactively labeled cloned fragments, representing virtually the entire HSV-1 genome, were individually hybridized to RNA in sections of trigeminal ganglia taken from rabbits during the latent phase of infection with HSV-1 (McKrae). Our results suggest that two discrete latency-related RNAs (LR-RNAs) may be pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
153
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(169 citation statements)
references
References 30 publications
9
153
2
Order By: Relevance
“…(Figure 1). The LAT RNA has been described in every member of the alphaherpesvirus subfamily [59,60], including VZV [9]. We confirmed the existence of four previously detected lytic isoforms of VLT (VLT ly ) of which two are TSS isoforms, one is a splice variant and one is both a TSS isoform and a splice variant (Figure 4, Supplementary Table 2).…”
Section: Non-coding Transcriptssupporting
confidence: 85%
“…(Figure 1). The LAT RNA has been described in every member of the alphaherpesvirus subfamily [59,60], including VZV [9]. We confirmed the existence of four previously detected lytic isoforms of VLT (VLT ly ) of which two are TSS isoforms, one is a splice variant and one is both a TSS isoform and a splice variant (Figure 4, Supplementary Table 2).…”
Section: Non-coding Transcriptssupporting
confidence: 85%
“…A more analogous example is the herpes simplex virus, where the ICPO gene sequence is transcribed in bot,h directions. The newly discovered anti-sense transcript, or latency-associated transcript,, is the only virus transcript present in latently infected neurons (27)(28)(29)(30)(31)(32).…”
Section: Two Newly Identified Overlapping Open Reading Framesmentioning
confidence: 99%
“…Although the present study used full-length cloned HSV DNA and does not indicate which genomic fragments are retained in the cornea during latent HSV infection, laboratory studies on neuronal tissues by other investigators (Stevens et al 1987;Croen et al 1987;Rock et al 1987;Gordon et al 1988) have indicated that the alpha HSV ICPO genome region (from the internal repeated region of the HSV genome) is involved in establishing, maintaining and possibly reversing the viral latency state. Their studies indicate that anti-sense HSV RNA (HSV RNA complementary to the alpha ICPO genome region) appears essential for maintaining latency and that sense HSV RNA appears essential in reactivation and lytic disease.…”
Section: Discussionmentioning
confidence: 86%
“…Tissue co-culture and immunofluorescent data have allowed recovery of live virus (infectious) and demonstration of viral antigen in neuronal tissues. Now molecular biology techniques, specifically in situ, dot and slot blot hybridization assays, have demonstrated conclusively the presence of specific herpetic nucleic acid sequences, specifically the alpha ICPO genome region, and sense and antisense HSV RNA in trigeminal ganglia and in brain nucleic acid extracts (Stevens et al 1972(Stevens et al , 1987Cabrera et al 1980;Fraser et al 1981;Tenser et al 1982;Croen et al 1987;Rock et al 1987;Gordon et al 1988). Certainly, these neuronal trissues are a key source of virus in recurrent herpetic disease.…”
mentioning
confidence: 99%